The specificity of sexual violence against women during the military dictatorship (1964-1985): Narrativas de mulheres à Comissão Nacional da Verdade (TEL Tempo, Espaço e Linguagem, 2025)
this text presents reports from women collected by Comissão Nacional da Verdade (CNV) who were victims of sexual violence and state repression during the military dictatorship (1964-1985). From the analysis of the transcripts of these reports, it was not only possible to verify the specificity of sexual violence when used against women, but also to notice a constant denial by the interviewees who, despite having suffered such violence, did not present themselves as victims of this type of violence.